2015
DOI: 10.1016/j.atherosclerosis.2015.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Expression of fibromodulin in carotid atherosclerotic plaques is associated with diabetes and cerebrovascular events

Abstract: Expression of fibromodulin in carotid atherosclerotic plaques is associated with diabetes and cerebrovascular events.Shami, Annelie; Tengryd, Christoffer; Asciutto, Giuseppe; Bengtsson, Eva; Nilsson, Jan; Hultgårdh, Anna; Goncalves, Isabel Link to publication Citation for published version (APA): Shami, A., Tengryd, C., Asciutto, G., Bengtsson, E., Nilsson, J., Hultgårdh, A., & Goncalves, I. (2015). Expression of fibromodulin in carotid atherosclerotic plaques is associated with diabetes and cerebrovascular ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Fibromodulin and lumican are two KS-containing PGs that are found in human arteries and human atherosclerotic plaques (see review [6]). Both mRNA transcripts and core proteins of these KSPGs have been identified in vascular lesions, including diffuse intimal thickening, fatty streaks, complete atheroma with fibrous plaque and complicated lesions [6, 234, 235]. While there is considerable overlap in the distribution of these two PGs, it is of interest that lumican is deposited adjacent to lipid-filled macrophages in fibrolipid-filled lesions.…”
Section: Lumican and Fibromodulinmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibromodulin and lumican are two KS-containing PGs that are found in human arteries and human atherosclerotic plaques (see review [6]). Both mRNA transcripts and core proteins of these KSPGs have been identified in vascular lesions, including diffuse intimal thickening, fatty streaks, complete atheroma with fibrous plaque and complicated lesions [6, 234, 235]. While there is considerable overlap in the distribution of these two PGs, it is of interest that lumican is deposited adjacent to lipid-filled macrophages in fibrolipid-filled lesions.…”
Section: Lumican and Fibromodulinmentioning
confidence: 99%
“…Fibromodulin also accumulates in atherosclerotic plaques and like lumican accumulates in macrophage-rich areas [234, 241]. Fibromodulin, like decorin, interacts with TGFβ1 and, when expressed in a vein graft failure organ culture model, fibromodulin caused a decrease in TGFβ1 and a reduction of neointimal hyperplasia of the vein graft [242].…”
Section: Lumican and Fibromodulinmentioning
confidence: 99%
“…Furthermore, an analysis to determine the key drivers of RGN 39 revealed that its top hierarchical key driver is CYTL1 —which is among the list of 120 CD90+ adventitial MSC genes of interest ( Figure 7 C). Moreover, several genes directly downstream of CYTL1 in RGN 39 have known connections to atherosclerosis or CAD, including MMP2 ( Liu et al., 2006 ), FMOD ( Fibromodulin ) ( Shami et al., 2015 ), CPNE4 ( Lee et al., 2015 ), and CD55 ( Leung et al., 2009 ) ( Figure 7 C). An additional key driver of RGN 39, ANOS1 , was also among our 120 CD90+ adventitial MSC genes of interest ( Figure 7 C).…”
Section: Resultsmentioning
confidence: 99%
“…In ApoE‐deficient mice, the lack of fibromodulin has shown to reduce plaque formation . Furthermore, fibromodulin also showed to be associated with abnormal collagen fibres in the vulnerable plaque and decreased lipid retention in the vascular ECM .…”
Section: Proteoglycansmentioning
confidence: 99%